Partial restoration of immune response in Hepatitis C patients after viral clearance by direct-acting antiviral therapy. - Meritxell Llorens-Revull; Maria Isabel Costafreda; Angie Rico; Mercedes Guerrero-Murillo; Maria Eugenia Soria; Sofía Píriz-Ruzo; Elena Vargas-Accarino; Pablo Gabriel-Medina; Francisco Rodríguez-Frías; Mar Riveiro-Barciela; Celia Perales; Josep Quer; et al. (PLoS ONE)
Background & aims HCV CD4+ and CD8+ specific T cells responses are functionally impaired during chronic hepatitis C infection. DAAs therapies eradicate HCV infection in more than 95% of treated patients. However, the impact of HCV elimination on immune responses remain controversial. Here, we aimed to investigate whether HCV cure by DAAs could reverse the impaired immune response to HCV. Methods We analyzed 27 chronic HCV infected patients undergoing DAA treatment in tertiary care hospital, and we determined the phenotypical and functional changes in both HCV CD8+ and CD4+ specific T-cells before and after viral clearance. PD-1, TIM-3 and LAG-3 cell-surface expression was assessed by flow cytometry to determine CD4+ T cell exhaustion. Functional responses to HCV were analyzed by IFN-Ɣ ELISPOT, intracellular cytokine staining (IL-2 and IFN-Ɣ) and CFSE-based proliferation assays. Results We observed a significant decrease in the expression of PD-1 in CD4+ T-cells after 12 weeks of viral clearance in non-cirrhotic patients (p = 0.033) and in treatment-naive patients (p = 0.010), indicating a partial CD4 phenotype restoration. IFN-Ɣ and IL-2 cytokines production by HCV-specific CD4+ and CD8+ T cells remained impaired upon HCV eradication. Finally, a significant increase of the proliferation capacity of both HCV CD4+ and CD8+ specific T-cells was observed after HCV elimination by DAAs therapies. Conclusions Our results show that in chronically infected patients HCV elimination by DAA treatment lead to partial reversion of CD4+ T cell exhaustion. Moreover, proliferative capacity of HCV-specific CD4+ and CD8+ T cells is recovered after DAA's therapies.